Treatment With Methotrexate Associated With Lipid Core Nanoparticles Prevents Aortic Dilation in a Murine Model of Marfan Syndrome - Guido, Maria Carolina; Lopes, Natalia de Menezes; Albuquerque, Camila Inagaki; Tavares, Elaine Rufo; Jensen, Leonardo; Carvalho, Priscila de Oliveira; Tavoni, Thauany Martins; Dias, Ricardo Ribeiro; Pereira, Lygia da Veiga; Laurindo, Francisco Rafael Martins; Maranhão, Raul Cavalcante (Frontiers in Cardiovascular Medicine, 2022)
In Marfan syndrome (MFS), dilation, dissection and rupture of the aorta occurs. Inflammation can be involved in the pathogenicity of aortic defects and can thus be a therapeutic target for MFS. Previously, we showed that the formulation of methotrexate (MTX) associated with lipid nanoparticles (LDE) has potent anti-inflammatory effects without toxicity. To investigate whether LDEMTX treatment can prevent development of aortic lesions in MFS murine model. MgΔloxPneo MFS (n=40) and wild-type (WT, n=60) mice were allocated to 6 groups weekly injected with IP solutions of: 1) only LDE; 2) commercial MTX; 3) LDEMTX (dose=1mg/kg) between 3rd-6th months of life. After 12 week-treatments, animals examined by echocardiography and euthanatized for morphometric and molecular studies. MFS mice treated with LDEMTX showed narrower lumens of aortic arch, ascending and descending aorta. LDEMTX reduced fibrosis and number of dissections in MFS but not number of elastic fiber disruptions. In MSF mice, LDEMTX treatment lowered protein expression of pro-inflammatory factors CD68 (macrophages), CD3 (T-lymphocytes) and TNF-α, apoptotic factor cleaved-caspase 3 and type 1 collagen and lowered the protein expression of TGF-β, ERK1/2 and SMAD3. Protein expression of CD68 and CD3 had positive correlation with area of aortic lumen (r2=0.36;p<0.001), suggesting the importance of inflammation in causative mechanisms of aortic dilation. Enhanced adenosine availability by LDEMTX was suggested by higher aortic expression of A2a adenosine receptor and lower adenosine deaminase expression. Commercial MTX had negligible effects. LDEMTX prevented the development of MFS-associated aortic defects and can thus be a candidate for testing in clinical studies.